Listrik mikro hidro berdasarkan Potensi debit andalan sungai batanghari kota jambi - Hendi Matalata (Universitas Batanghari Jambi, 2018)
The city of Jambi is an area batanghari river, the study of the utilization of renewable energy, especially hydro power through the tributaries should be considered for the planning of Micro Hydro Power Plant (PLTMH). Water conditions that can be utilized as electricity generating resources have a certain flow capacity and altitude of their drainage system. A major problem in hydroelectric generation is the availability of river water discharge as a propulsion energy. Therefore, certain techniques are needed to predict the potential flow of river water at all times or the river's main discharge that can be used for hydro-electric power generation, no long-term rainfall and critical watershed conditions can cause water flow the stream becomes small and even becomes dry. Manual river flow measurements over time can only represent the volume of river flow at the time of measurement. Changes that occur due to the occurrence of rain at a later time, or decrease in river discharge due to decreased soil water savings, can not be monitored properly it is necessary to plan a continuous discharge for the capacity of generator turbine rotation by calculating the electrical capacity of the generator which can be generated optimally